Luteolytic and embryotrophic effects of progesterone supplementation in beef cattle - Martins, Thiago (2018)
Inadequate uterine environment is one of the main causes of pregnancy failure in cattle. Progesterone (P4) supplementation during early diestrus may either induce a receptive uterine status or shorten luteal lifespan and reduce fertility. Regulation that leads to either outcome is currently unclear. In this thesis, four studies were conducted to test the main hypothesis that the pre-implantational conceptus plays a major role on preventing P4-luteolytic effects in Bos indicus beef cows, due the supplementary P4. In a fifth study the importance of the uterine luminal milieu on the establishment of pregnancy was evaluated. P4 was supplemented by injecting 150 mg of long acting injectable P4 (iP4) on 3 days post-ovulation. In the last study, uterine luminal flushings were performed on days 1, 4 and/or 7 post-estrus, aiming to deplete the uterine milieu. In this thesis, we evidenced that uterus played a key role on determining the iP4-luteolytic response. In this sense, first study revealed that higher uterine exposure to estradiol (E2) during pre-ovulatory period prevented P4-luteolytic effect, but did not increase overall pregnancy outcome. Further analysis, revealed that optimal uterine estradiol exposure is required for beneficial effects of iP4. Cows with large preovulatory follicle or with small follicle, but exposed to the exogenous estradiol presented higher pregnancy rates. Next, we demonstrated that iP4 hindered CL formation, but this had a minor impact on iP4-induced luteolysis. About half of iP4 supplemented cows presented early luteolysis, which occurred by day 15 post-ovulation. Role of the embryo to inhibit iP4-induced early luteolysis relied on its capability to establish pregnancy. In the third study, we demonstrated that iP4-inhibition of growth of the first-wave dominant follicle was related to early luteolytic onset, and this was independent of number of waves in the cycle (two vs. three). Three-wave cycles favored embryonic capacity to inhibit early luteolysis. In the fourth study, we failed to demonstrate that P4 supplementation supported embryonic survival. This was despite of the transfer of 5 embryos to each recipient cow to maximize embryonic signaling. In the last study we disturbed the composition of the uterine environment and negatively affected, but did not abolish, embryonic survival. Overall, from the results obtained in the course of this thesis, we conclude that variability in fertility rates after P4 supplementation, are in part attributable to the complexity of uterine function programming by sex steroids, rather than caused by the incidence of early luteolysis. Furthermore, we highlighted that a sub-optimal composition of the uterine environment is a major contributor to embryonic losses in beef cattle.